Legal Protection of Children as Witnesses in Criminal Cases (Study at the Belawan District Attorney) - Yenni Maya Sari; Alpi Sahari; Ahmad Fauzi (International Journal Reglement & Society (IJRS), 2022)
The role of witnesses in every trial of criminal cases is very important because witness statements can influence and determine the tendency of judges' decisions. This study aims to analyze the position of children as witnesses in proving criminal cases, analyze the process of examining children as witnesses in the juvenile criminal justice system and analyze the legal protection of children as witnesses in criminal cases. This research method uses normative research with data types consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the study are legal protection for children as witnesses in criminal cases as stated in Law Number 35 of 2014 concerning Child Protection, Law Number 31 of 2014 concerning Protection of Witnesses and Victims and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The role of the prosecutor in presenting witnesses is related to the case to be examined in court. The main task of the Prosecutor's Office in the criminal justice system in Indonesia is prosecution, and vice versa, prosecution is the authority of the Prosecutor's Office. The authority to prosecute is the embodiment of the Dominus Litis Principle. However, the obstacles encountered in presenting children as witnesses are in establishing communication with children as witnesses in criminal cases